KARAKTERISTIK MUTU SIRUP RUMPUT LAUT (Eucheuma spinosum) - Anharullah, La Ode Muhammad; Haslianti, Haslianti; Asyik, Nur (Jurnal Fish Protech, 2021)
ABSTRACT         The aim of this study was to determine the quality characteristics of seaweed Syrup (Eucheuma spinosum). This study used a Completely Randomized Design (CRD) consisting of 3 treatments, namely: P1 = 100 gr seaweed: 200 gr sugar: 3.5 L water: CMC 0.3 gr, P2 = 120 gr seaweed: 200 granulated sugar gr: water 3,5 L: CMC 0,3 gr, P3 = Seaweed 140 gr: sugar 200 gr: water 3,5 L: CMC 0,3 gr: with three times replications. Data from observations were analyzed using ANOVA (Analysis of Variance) at a level of 95%, if there is a significant difference (P> 0.05), further tests were carried out with the DMRT (Duncan Multiple Range Test) tests at a 95% confidence level. The results obtained showed that the concentration of seaweed (E. spinosum), water, and taste did not significantly affect the aroma and taste of seaweed syrup. The best treatment was in the treatment of P1 with a scent value of 3.46 with a rather like category, and P1 for a taste of 3.46 with a somewhat like category. The chemical value of seaweed syrup is the value of water content ranging from 38.96% -43.21%, ash content ranges from 0.82-1.34%. Keywords: Syrup, seaweed (Eucheuma spinosum), chemistry and sensoryABSTRAKTujuan penelitian ini adalah untuk mengetahui Karakteristik Mutu Sirup Rumput Laut (Eucheuma spinosum). Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) yang terdiri dari 3 perlakuan yaitu : P1 = Rumput laut 100 gr : gula pasir 200 gr : air 3,5 L : CMC 0,3 gr, P2 = Rumput laut 120 gr : gula pasir 200 gr: air 3,5 L : CMC 0,3 gr, P3 = Rumput laut 140 gr : gula pasir 200 gr : air 3,5 L : CMC 0,3 gr : dan ulangan sebanyak tiga kali. Data hasil pengamatan dianalisa menggunakan ANOVA (Analysis of Variance) pada taraf 95%, apabila terdapat beda nyata (P>0,05) maka dilakukan uji lanjut dengan uji DMRT (Duncan Multiple Range Test) pada taraf kepercayaan 95%. Hasil penelitian yang diperoleh menunjukkan bahwa Kosentrasi rumput laut (E. Spinosum), air dan rasa berpengaruh tidak nyata terhadap aroma dan rasa sirup rumput laut. Perlakuan terbaik terdapat pada perlakuan P1 dengan nilai aroma sebesar 3,46 dengan kategori  agak suka, dan P1 rasa 3,46 dengan kategori agak suka. Nilai kimia sirup rumput laut yaitu nilai kadar air berkisar 38,96%-43,21%, kadar abu berkisar 0,82-1,34%.Kata kunci: Sirup, rumput laut (Eucheuma spinosum), kimia dan sensori